Penerapan Model Flipped Classroom Untuk Meningkatkan Hasil Belajar IPA Pada Siswa Kelas 4 MIN 2 Kota Bengkulu - Rindu Hati (Yayasan Darusssalam Bengkulu, 2021)
The low science learning outcomes of students in the transition period after the Covid-19 pandemic. At this time, 50% of learning activities can be done at home online and 50% face-to-face at school. The flipped classroom learning model is one of the right learning model solutions because it combines the two learning activities. The purpose of this study was to describe the application of the flipped classroom model to improve science learning outcomes in fourth grade students of MIN 2 Bengkulu City. The research method used is Classroom Action Research. The research subjects were students of 4th grade C Madrasah Ibtidaiyah Negeri 2 Bengkulu City, totaling 30 students. Data collection techniques used observation sheets and science learning outcomes tests at the end of each cycle. The results showed that there was an increase in the percentage of science learning outcomes from 53% in pre-cycle to 73% in cycle 1 and then increased to 93.3% in cycle 2. So it can be concluded that the application of the flipp classroom learning model is very appropriate to improve science learning outcomes in class students of 4th grade Madrasah Ibtidaiyah Negeri 2 Bengkulu City